The ovoid amphorae in the Central and Western Mediterranean : between the last two centuries of the Republic and the early days of the Roman Empire - García Vargas, Enrique,; De Almeida, Rui Roberto,; González Cesteros, Horacio, 1978-; Sáez Romero, Antonio M., (Roman and late antique Mediterranean pottery ;, 2019)
Based on the proceedings of a workshop held at Seville University in 2015, this book looks at several series of amphorae created in the Late Republican Roman period, sharing a generally ovoid shape in their bodies - a group of material which, until now, has rarely been studied.